Brain antioxidant status and gene expressions of nicotinic and dopamine receptors are improved by black seed oil administration in cigarette smoke or nicotine vapour-exposed rats (Nigerian Journal of Physiological Sciences, 2023)
Background: Smoking is associated with dysregulation of the antioxidant system and addiction.Aim: This study sought to ascertain the effect of Nigella Sativa (NS) oil on the antioxidant system, nicotine/tobacco addiction as well as the expressions of α4β2 nicotinic (nAChR) and dopamine type-2 (DRD2) receptors in selected brain regions of the rat.Methods: Thirty male Sprague-Dawley rats were divided into 6 groups comprising of vehicle-treated control, NS oil only, Smoke only, Smoke + NS oil, Nicotine only and Nicotine + NS oil. Animals were passively exposed to cigarette smoke or nicotine vapour for 12 weeks, however, NS oil treatment commenced from 9th-12th week of the experimental duration.Results: Nicotine vapour and cigarette smoke-induced increase in cotinine level were significantly ameliorated by NS treatment. Cigarette smoke or nicotine vapour exposure significantly (p